Identification of basic elements for car seat design - Ling, Teck Huat (2014)
Fatigue is prevalent among drivers especially during long distance driving, and is often classified as a predominant contributor to road accidents, although its contribution to individual cases is tough to measure, and is often not reported as the cause of the accident. Driver fatigue is often associated with sitting discomfort, where much emphasis is placed by car manufactures to refine the design of their car seats, to improve sitting comfort as well as to reduce driver fatigue. The objective of this study is to determine the relationships between car seat design elements and driver fatigue, as well as how age related differences will affect this relationship. This study involve a combination of a focus group study and a lab-based experimental study, where basic elements for car seat design will be identified using the focus group approach involving design experts and researchers from TUM Create Centre. Taxonomy for describing the identified car seat design elements for each of the selected car seats are developed by the design experts at the end of the focus group approach, based on information collated from topics such as; car seats contours and features, car seats material, as well as the positioning, inclination and seating angle of the car seats. Information collated have also shown and proven that driver's fatigue can be indirectly affected by major factors such as; the amount of cushions used for the car seat, the hardness level of the cushion used for the car seat, the size of the car seat, the side area of backrest, as well as the side area of the seat cushion.